Gibraltar : Detailed Assessment Report of Observance of the Basel Core Principles. (IMF Staff Country Reports; Country Report ;, 2007)
Gibraltar's Detailed Assessment Report of the Observance of the Basel Core Principles is examined. The principal risks are reputational risk, both for the Gibraltar authorities and for the banks, as the bulk of the assets managed are off the balance sheet with the investment risk carried by the client. Credit risk is largely limited to residential mortgage lending and is heightened by the rapid rise in prices both in Southern Spain and in Gibraltar itself.